2012
DOI: 10.1017/jns.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Asperuloside stimulates metabolic function in rats across several organs under high-fat diet conditions, acting like the major ingredient ofEucommialeaves with anti-obesity activity

Abstract: Eucommia leaves (Eucommia ulmoides Oliver) contain chlorogenic acid (a caffeic acid derivative) and geniposidic acid and asperuloside (ASP), iridoid glucosides used in beverages. We used a metabolic syndrome rat model, produced by feeding a 35 % high-fat diet (HFD), to examine potential anti-obesity and anti-metabolic syndrome effects and mechanisms of chronic administration of ASP. These effects were compared with Eucommia leaf extract (ELE), the positive control, which exhibits anti-obesity effects. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 21 publications
5
37
0
Order By: Relevance
“…Asperuloside (ASP) is indicated as the major ingredient of ELE; it contributes to its anti-obesity effect [8,11]. In the previous study, the administration of ELE or ASP significantly reduced the ratio of WAT weight to the body weight in perirenal WAT and tended to reduce this ratio in epididymal WAT [9,11]. The aim of this study is to ascertain whether ELE and its major component, ASP, affect the size of adipocytes in WAT.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Asperuloside (ASP) is indicated as the major ingredient of ELE; it contributes to its anti-obesity effect [8,11]. In the previous study, the administration of ELE or ASP significantly reduced the ratio of WAT weight to the body weight in perirenal WAT and tended to reduce this ratio in epididymal WAT [9,11]. The aim of this study is to ascertain whether ELE and its major component, ASP, affect the size of adipocytes in WAT.…”
Section: Introductionmentioning
confidence: 98%
“…Eucommia leaf extract (ELE) has been reported to have various bioactive properties [3][4][5][6][7][8][9][10][11], such as anti-obesity effects [6][7][8][9][10][11]. Asperuloside (ASP) is indicated as the major ingredient of ELE; it contributes to its anti-obesity effect [8,11]. In the previous study, the administration of ELE or ASP significantly reduced the ratio of WAT weight to the body weight in perirenal WAT and tended to reduce this ratio in epididymal WAT [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory data previously reported that asperuloside stimulates metabolic function across several organs in rats under highfat diet conditions, which act as the major ingredient in the anti-obesity and anti-metabolic syndrome activities of ELE [19,36]. In addition, ELE has been found to cause the suppression of appetite, which is partly involved in an anti-obesity effect [37].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the study of Eucommia leaf extract (ELE) has been focused on its efficacy in maintaining human health. Reports on the biogenic effectiveness of ELE ingestion have identified the following benefits: 1) antihyperlipidemic effects that reduce visceral fat and suppress elevated levels of triglyceride and cholesterol in the blood [1][2][3][4][5][6][7]; 2) effects on bone, such as preventing the onset of postmenopausal osteoporosis and promoting calcium accumulation in osteoblasts [8][9][10]; 3) antihypertensive effects that slowly decrease blood pressure by maintaining the flexibility of the blood vessels and promoting arterial smooth muscle relaxation [2,11]; 4) rapid eye movement sleep and non-rapid eye movement sleep inducing effect [12]; and 5) preventative effects on ulcerative colitis by asperuloside, one of the major components of ELE [13]. Thus, ELE promotes systemic health.…”
mentioning
confidence: 99%